PENGGUNAAN TABIR SURYA BAGI KESEHATAN KULIT - Prima Minerva (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
Most activities are done outside the home often make the skin exposed to UV light. Exposure UV light excessively or in a long time can cause the occurrence of skin disorders such as Sunburn, premature aging, lowering skin immunity to skin cancer. In preventing the negative effects of UV light on the skin, various ways can be done such as by using a protector such as clothes, hats, glasses or umbrellas. But this physical protection is not sufficient because of the UV light penetrating power. Sunscreen is a skin care cosmetic that provides physical protection against UV light. Proper use of sunscreen and routine can protect the skin from the negative effects of UV light. This paper describes the effects of UV light on the skin, the function of sunscreen and the right use and compatible types sunscreen in maintaining skin health from the adverse effects of UV light.